SISTEM INFORMASI AKADEMIK UNIVERSITAS STIKUBANK (UNISBANK) SEMARANG BERBASIS WEB MOBILE (Information Technology and Telematics, 2014)
ABSTRACT Currently Stikubank University (Unisbank) Semarang already have Academic Information System (SIA) web-based, but the SIA only can be accessed using a computer device. When accessed using mobile devices the system does not display the output according to the mobile device screen. The goal of this research is to develop Academic Information services of Stikubank University (Unisbank) Semarang Web-based mobile. So that would make it easier for students to access the system anywhere and anytime as long as they are connected with Internet. The results of this study are Academic Information Systems of Unisbank Semarang, which can be accessed using a mobile device. This application is made using the PHP programming language and uses the framework Jquery Mobile Flat-UI as display layout. As for compaction retrieval by utilizing existing web services on University Stikubank (Unisbank) Semarang Keyword--web mobile, web service, Academic Information System.